Staphylococcus cohnii infection diagnosed by metagenomic next generation sequencing in a patient on hemodialysis with cirrhotic ascites: a case report - Lei, Yu; Guo, Qiaozhen; Liu, Jingmei; Huang, Huanjun; Han, Ping (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Patients with spontaneous bacterial peritonitis (SBP) often just receive empirical antibiotic therapy, as pathogens can be identified in only few patients using the techniques of conventional culture. Metagenomic next generation sequencing (mNGS) is a useful tool for diagnosis of infectious diseases. However, clinical application of mNGS in diagnosis of infected ascites of cirrhotic patients is rarely reported. Case presentation: A 53-year-old male with cirrhosis on regular hemodialysis presented with continuous abdominal pain. After treatment with empiric antibiotics, his inflammatory parameters decreased without significant relief of abdominal pain. Finally, based on ascites mNGS detection, he was diagnosed as infection of Staphylococcus cohnii (S.cohnii), a gram-positive opportunistic pathogen. With targeted antibiotic treatment, the bacterial peritonitis was greatly improved and the patient’s abdominal pain was significantly alleviated. Conclusions：When conventional laboratory diagnostic methods and empirical antibiotic therapy fail, proper application of mNGS can help identify pathogens and significantly improve prognosis and patients’ symptoms.